Skin autofluorescence and peripheral neuropathy four years later in type 1 diabetes. Issue 2 (18th July 2016) - Rajaobelina, K; Farges, B; Nov, S; Maury, E; Cephise‐Velayoudom, FL; Gin, H; Helmer, C; Rigalleau, V
Abstract: Objective: Advanced glycation end products (AGEs) are involved in diabetes complications. We aimed to investigate whether the accumulation of AGEs measured by skin autofluorescence (sAF) was associated with signs of diabetic peripheral neuropathy and to sensitivity, pain, motor and autonomic function 4 years later in patients with type 1 diabetes. Methods: At baseline, 188 patients (age 51 years, diabetes duration 22 years) underwent skin autofluorescence measurement using the AGE Reader. Four years later, signs of diabetic peripheral neuropathy were defined as the presence of neuropathic pain and/or feet sensory loss or foot ulceration. Neurological tests were systematically performed: vibration perception threshold by neuroesthesiometry, neuropathic pain by the Douleur Neuropathique en 4 Questions score, muscle strength by dynamometry and electrochemical skin conductance. Multivariate analyses were adjusted by age, sex, height, body mass index, tobacco, HbA1c, diabetes duration, estimated glomerular filtration rate and albumin excretion rate. Results: At the 4‐year follow‐up, 13.8% of patients had signs of diabetic peripheral neuropathy. The baseline sAF was higher in those with signs of diabetic peripheral neuropathy (2.5 ± 0.7 vs 2.1 ± 0.5 arbitrary units (AU), p  < 0.0005). In the multivariate analysis, a 1 SD higher skin autofluorescence at baseline was associated with an increased risk of signs of neuropathy (OR = 2.68, p  = 0.01). All of the neurological tests were significantly altered in the highest quartile of the baseline sAF (>2.4 AU) compared with the lowest quartiles after multivariate adjustment. Conclusion: This non‐invasive measurement of skin autofluorescence may have a value for diabetic peripheral neuropathy in type 1 diabetes and a potential clinical utility for detection of diabetic peripheral neuropathy. Copyright © 2016 John Wiley & Sons, Ltd.